Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M195 - Jörg Pross; André Bahr; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M195 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 10.11.2023 - 02.12.2023 from Piraeus - Piraeus (Greece) in the Mediterranean Sea. The major aim of M195 ("CYRTACI" – Climate Dynamics and Ecosystem Change during the Rise of Mediterranean Civilizations) was to recover core material that will allow to investigate changes in terrestrial and marine ecosystems in the Mediterranean during the rise of human civilizations in that region. Data were recorded in the EEZ of Greece. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.